Age-related Changes in Training Stimuli and Performance in Masters Swimmers - Lapierre, Stephanie S.; Baker, Brett D.; Tanaka, Hirofumi (International Journal of Sports Medicine, 2018)
Age-related decreases in performance are thought to be driven by decreases in exercise training stimuli. We determined the influence of changes in training stimuli with advancing age on swimming performance using cross-sectional and longitudinal data analyses. Totals of 692 and 98 competitive swimmers belonging to the US Masters Swimming Association were analyzed in cross-sectional and longitudinal analyses. Swimming times increased with advancing age, and age was the strongest predictor of swimming performance, followed by training volume, in both the cross-sectional and longitudinal analyses. In the cross-sectional data analyses, an increase in training volume by 10 km/month, was associated with improved performance by 0.69 s regardless of age. In the longitudinal analyses, training volume was not a significant predictor for younger swimmers. In middle-aged swimmers, however, increases in training volume resulted in faster swimming times, and its effect was more pronounced in older swimmers. We concluded that there was a graded positive relationship between yearly increases in training volume and improved swimming performance, and that such effects were greater with advancing age.
Keywords: aging; exercise training; athletic performance; swimmers